1998
DOI: 10.3758/bf03199163
|View full text |Cite
|
Sign up to set email alerts
|

The influence of artificial paths and landmarks on the foraging behavior of Norway rats (Rattus norvegicus)

Abstract: In two experiments, we explored how the foraging behavior of Norway rats was influenced by different arrangements of artificial paths and vertical landmarks, The rats used the paths successively less for orienting to food in treatments in which paths led to food but were crooked, in which paths led only halfway to food, and in which paths were misaligned with respect to food. The arrangement of paths influenced the rats' rate of energy intake in the beginning of the experiment, whereas the arrangement of beaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 10 publications
2
17
0
1
Order By: Relevance
“…On the basis of our data and those of Roche and Timberlake (1998), the tactic that appeared most important was trail following represented in the form of traveling along arms and the arena wall. The tactics of distance minimizing, centralplace search, and random search were not influential or, at best, were subservient to the tactic of trail following.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…On the basis of our data and those of Roche and Timberlake (1998), the tactic that appeared most important was trail following represented in the form of traveling along arms and the arena wall. The tactics of distance minimizing, centralplace search, and random search were not influential or, at best, were subservient to the tactic of trail following.…”
Section: Discussionmentioning
confidence: 56%
“…This preference may be due to a dependence of locomotion on visual and tactual contact with vertical edges (see Munn, 1950;Roche & Timberlake, 1998;Timberlake, Leffel, & Hoffman, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example in the case of efficient maze searching, Timberlake (1983a) reviewed and extended previous data showing that rats acquire straight-alley running in the absence of any food reward. Timberlake and White (1990) showed that rats acquired efficient search of a radial-arm maze in the absence of food, while Hoffman et al (1999) and Timberlake et al (1999) and Roche and Timberlake (1998) showed that rats still acquired arm-following even when the arms of a radial maze were placed flat on the floor so other search patterns were possible and more efficient.…”
Section: O6erdetermined Respondingmentioning
confidence: 99%
“…For example, food-storing birds and rats use flexible hierarchies of spatial learning, the expression of which changes with circumstances and previous experience (e.g., Brodbeck, 1994;Kamil & Jones, 2000;Roche & Timberlake, 1998;Shettleworth & Sutton, 2005). Observations of free-ranging rats also support the operation of multiple spatial mechanisms in establishing and using trails connecting burrows and feeding areas (Calhoun, 1962;Leonard & McNaughton, 1990).…”
mentioning
confidence: 99%